The effect of toothpaste with reduced concentration of fluoride-containing sodium trimetaphosphate and polyols on initial enamel erosion - de Toledo, Priscila Toninatto Alves [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Cannon, Mark Lloyd; Sakamoto, Amanda Eliane [UNESP]; Pedrini, Denise [UNESP] (Springer Nature, 2022)
Objectives: This in vitro study evaluated the efficacy of toothpaste containing fluoride (F), sodium trimetaphosphate (TMP), and xylitol and erythritol (XE) to inhibit or repair initial enamel erosion lesions. Materials and methods: Bovine enamel blocks (n = 120) were selected according to surface hardness (SH) and randomly divided into 5 experimental groups (n = 24 blocks/group): Placebo (no F, TMP, XE); 1100 ppm F; 16% xylitol + 4% erythritol (XE); 200 ppm F + 0.2% TMP (200 ppm F/TMP); and 200 ppm F + 0.2% TMP + 16% xylitol + 4% erythritol (200 ppm F/TMP/XE). The sound and softened blocks were immersed in toothpaste slurry in human saliva for 2 min. The blocks were then submitted to 4 erosive challenges in citric acid (0.75%, pH 3.5), each challenge for 1 min, with stirring. The SH of the blocks was determined after treatment (t) and after the 4 erosive challenges. In addition, the precipitates were analyzed by scanning electron microscopy (SEM). Variables were submitted to a two-way repeated-measures analysis of variance followed by a Student–Newman–Keuls test (p < 0.05). Results: Toothpaste containing 200 ppm F/TMP/XE led to the highest protective and repair effect compared to the other groups (p < 0.001). The protective and repair effect was XE > 200 ppm F/TMP > 1100 ppm F > placebo (p < 0.001). All groups produced precipitates with a thicker layer for XE and TMP groups. Conclusions: Toothpaste containing 200 ppm F, TMP, and polyols demonstrated a superior protective and repair effect in initial enamel erosive lesions in vitro. Clinical relevance: Toothpaste containing F and polyols could be an advantage in patients affected by dental erosion, due to its higher preventive potential, mainly in individuals who frequently drink acidic beverages. However, future studies are needed to confirm these results.
Keywords: Dentifrices; Fluorides; Phosphates; Polyols; Tooth erosion